Antioxidant properties of plant extracts for biodiesel stabilization - Laguta, I.V.; Stavinskaya, O.N.; Kuzema, P.O.; Ivannikov, R.V.; Anishchenko, V.N.; Linnik, О.P. (Reports of the National Academy of Sciences of Ukraine, 2021)
Using two different extraction procedures, eight ethanol plants extracts are obtained from the leaves of Magnolia X soulangeana Soul.-Bod., Magnolia kobus, and two samples of Camellia japonica L. The composition and antioxidant properties of the extracts are studied by means of high performance liquid chromatography, the Folin— Ciocalteu method, and DPPH test. Hydroxycinnamic acids and quercetin glicosides are found to be the main constituents of Magnolia extracts, while hydroxybenzoic acids and catechin derivatives prevailed in Camelia extracts. The composition of the extracts was also affected by extraction procedures; in general, the extracts obtained at 60 °C under ultrasonic treatment contained phenolic compounds of a higher quantity than the extracts prepared by boiling the leaves in 70 % ethanol at ~85 °C; the overall amount of phenolic compounds in the extracts was in a range of 50-150 mg/l. In spite of significant distinctions in the content of phenols, all the extracts were found to possess a very high antioxidant activity in both Folin—Ciocalteu and DPPH assays. The extracts were found to have the total phenolic index of 1.5-7.5. During 30 min of the reaction, seven of eight extracts inhibited more than 50 % of DPPH radicals under standard test conditions, even being diluted by 10 times. The extract of Camellia japonica L. with the highest antioxidant ability was also tested as an additive to stabilize the biodiesel against oxidation. The stability of biodiesel prepared from Camelina sativa (L.) Crantz was studied according to accelerated procedure at 43 °C for four weeks, with the changes in the acid value of the samples being the criteria of fuel oxidation. The preliminary results showed that Camellia extract may be a promising stabilizing additive to reduce the biodiesel oxidation.